Constructivist Architecture of Zlatoust: The Urban Heritage of the 1920s–1930s - Bugrov, Konstantin D. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This paper deals with the historical and cultural heritage of an important industrial centre of the Urals, the city of Zlatoust, namely, its constructivist architecture which emerged during the age of the first five-year plans, and which remained out of researchers’ view. The specifics of the urban process of the industrialisation age in older industrial settlements of the Urals was defined by the deployment of new constructivist buildings in the existing dense urban environment and in the proximity to production sites. The author describes two key locations of new construction in detail. In the old centre, around the Square of the Third International and along Lenin Street, the old dominants were demolished in the early 1930s (cathedral, Lutheran church) and replaced by new ones (club, bank, fire station, 4-storey residential buildings). In the northern part of the town, the residential zone was developed by the Zlatoust Steel Mill, which was heavily reconstructed in the early 1930s, its settlement had a peculiar planning (terraces on the steep slope of a mountain). Drawing upon archival sources, the author traces the process of planning and construction of key residential and public buildings of Zlatoust (factory kitchen, public bath), shows the peculiarities of urban development in the industrial settlement in the Urals, and outlines the projects of particular structures as well as the course of construction. In the second half of the 1930s, the urban development of Zlatoust was stagnating, and most projects from this period (House of Specialists, House of the Soviets) remained on paper. The author specially describes the housing policy of the Zlatoust Steel Mill. Also, he demonstrates that Zlatoust was a leader among the old (pre-revolutionary) industrial settlements in terms of construction, however, due to the outpacing population growth, administrative changes in the second half of the 1930s and the complex natural landscape, the social infrastructure of the city remained underdeveloped. That, in turn, provoked an acute shortage of housing and communal crises during the Great Patriotic War. The constructivist heritage of Zlatoust was incapable of becoming a cultural symbol of the city in the second half of the twentieth century, and even suffered major losses associated with both the expansion of industrial sites and the outflow of the population from the old part of the settlement.